Silk industry in Kashmir Present Status Structural Challenges and Pathways to Sustainable Rural Livelihoods - Islam, Tasdeeq ul; Dar, Mohd Ashraf (International Journal of Aquatic Research and Environmental Studies, 2026)
Sericulture remains an important livelihood option in the Union Territory of Jammu and Kashmir (J&K), where limited agricultural opportunities and fragmented landholdings shape rural economies. This study examines the present status of the sector, with a focus on its structural constraints and potential pathways for sustainable rural livelihoods. The analysis draws on district-level secondary administrative data obtained through RTI, complemented by the Economic Survey 2024–25, Central Silk Board reports, and relevant scholarly literature. The findings indicate a mixed trajectory. Cocoon production increased by 17.6%, rising from 6.99 lakh kg in 2022–23 to 8.22 lakh kg in 2023–24, reflecting renewed growth in primary production. However, this progress is constrained by persistent gaps in post-cocoon processing and value addition. Nearly 60% of cocoon output is exported outside the region, leading to an estimated annual loss of over ₹20 crore in potential value. While women constitute more than 53% of the workforce, their participation in formal economic activities remains limited. The study highlights the need to strengthen processing infrastructure, improve data governance, and promote women-led enterprises to realize the full potential of sericulture as a sustainable and inclusive livelihood system.